Cognitive neuroscience and psychotherapy : network principles for a unified theory - Tryon, Warren W.; ScienceDirect eBooks (Amsterdam : Elsevier Academic Press, 2014)
Cognitive Neuroscience and Psychotherapy provides a bionetwork theory unifying empirical evidence in cognitive neuroscience and psychopathology to explain how emotion, learning, and reinforcement affect personality and its extremes. The book uses the theory to explain research results in both disciplines and to predict future findings, as well as to suggest what the theory and evidence say about how we should be treating disorders for maximum effectiveness. While theoretical in nature, the book has practical applications, and takes a mathematical approach to proving its own theorems.
Chapter 10 -- Clinical Applications of Principle 2: Learning and Memory.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Cognitive neuroscience; Psychotherapy; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Cognitive neuroscience; Psychotherapy; Electronic books